Kemampuan berpikir kritis dalam pemecahan masalah matematika; Systematic Literatur Review - Mursidah Mursidah; Rizky Rosjanuardi; Dadang Juandi (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2023)
Critical thinking is critical analysis and assessment of problem to make decision. Critical thinking is essential aspect to improve students’ problem solving skills. The purpose of this research is to analyze qualitative studies on students' critical thinking skills in primary, secondary, tertiary and higher education, from 2013-2023. This research uses Syistematic Literature Review (SLR) which categorizes primary data from previous publications in proceedings journals, indexed by Sinta and Scopus. Data extraction was adjusted to the selection criteria, so that 27 articles were collected. Qualitative methods were used to analyze the data. Data grouping was based on publication year, education level, demographics, indexed journals, material analyzed, and research results. The results showed that research related to critical thinking skills became a trend in research conducted in 2013-2023 for algebra topics. Many studies related to critical thinking skills were conducted on the Asian continent. However, students' critical thinking skills are still low for all levels of education. Based on critical thinking indicators, students have difficulty in evaluating. This is because students do not really understand the basic concepts of mathematics. As a result, this is a concern for researchers and educators to conduct research related to students' critical thinking skills.